International trade and cultural diversity : a model of preference selection - Vankatesh Bala; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2004)
We consider the evolution of preferences when trade occurs between two countries. We show that if one country is much larger than the other, its preferences can eventually take over the preferences of the second country. This result may provide an explanation of why small countries sometimes exclude certain goods (especially those related to culture) from trade agreements. We also show that when the sensitivity of preferences to the relative price is high, the distribution of preferences can fluctuate cyclically over time.
Keywords: D80; 330; preferences; evolution; culture; replicator dynamics; international trade; Außenwirtschaft; Kleines-offenes-Land; Präferenztheorie; Kultur; Landesgröße; Evolutionsökonomik; Theorie